(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Death is not an event; it is a process. 10% of all deaths are sudden and unexpected deaths. 45% to 50% of sudden deaths involve the cardiovascular system. Heart diseases are one of the most common causes of sudden death. The body of the deceased is brought for autopsy in cases of sudden death to ascertain the cause of death. the identification of early myocardial infarcts at autopsy poses a challenge to the autopsy surgeon, since unequivocal gross changes of infarcts do not become evident for the first twenty-four to forty-eight hours following the ischemic injury to myocardium. Clinicians use cardiac biomarkers such as CPK, CPK-MB, Troponin I&T, to screen living patients for acute MI. Hence if these markers could be measured from the pericardial fluid and if found to be high in cases of sudden death due to myocardial ischemia, they could prove a vital clue to establish the cause of death. Pericardial fluid is easy to collect, analyze and gives accurate results even, a long